Znaczenie funduszy strukturalnych i Funduszu Spójności dla rozwoju miasta Wrocławia - Świderski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The Cohesion Fund and structural funds were established in order to reduce developmental disproportions between the countries and regions of the European Community. EU funds play an important role in aiding less developed countries and regions. As such, the author’s aim is to determine the impact of EU funds on the development of the city of Wrocław. The present article is based on literature and empirical research, mainly the analysis of data from the City Hall of Wrocław and the government database on grants from EU funds. The outcome of the research indicates that the EU funds significantly influenced the implementation of projects and investments that contributed to improving the quality and living conditions of the residents of Wrocław, however, the author also notes the negative effects of the use of said EU funds, such as an increase in the city’s liabilities.
Keywords: Cohesion Fund; European Structural Funds; Wrocław; development